Assessing Crypto-Zakat’s Legal and Sharia Validity in Indonesia’s Digital Economy - Riyan Al Fajri (Penerbit Goodwood, 2026)
Purpose: This study investigates the legal and Sharia perspectives on the use of cryptocurrency in Indonesia’s digital economy, with a focus on its potential application for zakat payments. Methodology/Approach: Using a legal-normative and doctrinal approach, this study analyzes Indonesia's statutory regulations (e.g., Law No. 23 of 2011) and fatwas from major Islamic organizations. Secondary sources include academic articles and classical jurisprudence. Results/Findings: The findings reveal that while Indonesian law acknowledges cryptocurrency as a digital asset, it is not recognized as legal tender. In terms of Sharia law, there are differing opinions, with some Islamic scholars viewing cryptocurrency as haram due to the uncertainty (gharar) involved, while others accept it as a permissible asset if backed by tangible goods. However, the use of cryptocurrency for zakat payments is not authorized, though crypto-assets themselves could be subject to zakat if they meet specific conditions. Conclusion: Despite legal and religious constraints, cryptocurrency could be used for zakat if robust regulations are developed. This requires coordinated institutional, legal, and religious efforts. Limitations: This study is limited to normative and doctrinal analysis. It lacks empirical data from zakat institutions or users, which restricts its practical scope. Contribution: This research contributes to Islamic digital finance by offering a dual legal-religious analysis. It also provides policy insights for aligning Indonesia's financial regulations with Sharia principles.